2022
DOI: 10.3390/app12031544
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Bite Force Measured via Digital Bite Force Transducer in Subjects with or without Dental Implants—A Pilot Study

Abstract: The aims of the current study were as following: (1) to evaluate the maximal bite forces in patients with dental implants versus patients without dental implants, as measured by a digital bite force transducer (GM10); (2) to evaluate the influences of sex, age, and sleep/awake bruxism on the maximal bite forces of the two groups. Forty patients recruited to the study were divided into two groups: test group (“implant”) if they had one or more posterior restored implants and control group (“no-implant”) without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The mean unilateral bite force in the premolar area is 70% lower than the molar region, with an average of 210-420 N [42]. In another study [51], the mean value of the maximum bite force is around 353 N in men, while in women it is 218 N. In one study [50] discussing the effect of clenching intensity on the biting force in the premolar region, the results showed values from 450 to 660 N. According to our results, these designs cannot be used in case of clenching and bruxism. Occlusal forces rarely reach 45 N during normal chewing, equivalent to the mean of molar bite force [9].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mean unilateral bite force in the premolar area is 70% lower than the molar region, with an average of 210-420 N [42]. In another study [51], the mean value of the maximum bite force is around 353 N in men, while in women it is 218 N. In one study [50] discussing the effect of clenching intensity on the biting force in the premolar region, the results showed values from 450 to 660 N. According to our results, these designs cannot be used in case of clenching and bruxism. Occlusal forces rarely reach 45 N during normal chewing, equivalent to the mean of molar bite force [9].…”
Section: Discussionmentioning
confidence: 90%
“…According to the literature, the intraoral bite forces are in the range of 216-847 N [9,50]. The mean unilateral bite force in the premolar area is 70% lower than the molar region, with an average of 210-420 N [42].…”
Section: Discussionmentioning
confidence: 99%
“…The error values are not directly comparable because of the variable sensor designs, testing conditions, and error calculations used. Five studies used intraclass correlation coefficient to measure the repeatability of bite force measurements using force sensing resistors (ICC = 0.93) [ 46 ], a miniature load cell (ICC = 0.719) [ 112 ], or bite forks (ICC = 0.3–0.64 for inter-observer reliability and ICC = 0.63–0.96 for intra-observer reliability) [ 47 , 48 , 109 ]. One study used Kappa analysis to calculate inter-device reliability (Kappa = 0.8132 ± 0.0544 and 0.8303 ± 0.0538) [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of BF allows us to determine the average BF values of a given population, thus helping us choose the most suitable and resistant materials during prosthetic rehabilitation. Based on Takaki et al’s study, in which they reported a mean BF of 285.01 N for women and 253.99 N for men [ 31 ], and Levartovsky et al’s study, in which they reported an average BF of between 258.5 N and 175.8 N [ 32 ], we used an average BF reference value of 250 N. Taking into account this average BF value and analyzing the results obtained, we can see that all structures with a 6 mm cantilever required a force greater than the average reference value for fracture to occur, unlike structures with a 10 mm cantilever, of which only three structures resisted forces greater than 250 N (one in PT and two in IZT). However, Van Vuuren et al reported an average BF of 430.4 N [ 33 ], and, taking this value into account, we can see that only structures with a 6 mm cantilever can resist this average BF, given that the mean fracture values found in this study were 437.54 N in PT and 447.05 N in IZT.…”
Section: Discussionmentioning
confidence: 99%